KEISTIMEWAAN MORFOLOGI UNTA PERSPEKTIF AL-QUR’AN DAN SAINS - Syahidah, Ariny; Efendi, Efendi; Faizin, Faizin; syahidah, arinysyahidah (STAI Syubbanul Wathon Magelang, 2025)
Allah, the Almighty Creator who bears the name Al-Qadir (The Omnipotent), holds absolute power over all His creations. Nothing is worthless or in vain in His eyes. In Surah Al-Ghashiyah verse 17, Allah points to the camel as an object worthy of deep observation and reflection: